Physicochemical characteristics of Bt (Seeni-1) Vs. local hamid cultivar cotton seed oils - Yassin, Atif A. A.; Abdelrahman, Samah A. M.; EL-Hassan, Ayia MA; Mirghani, Mohamed Elwathig Saeed; Bashir, Nabil Hamid Hassan (ECronicon Open Access, 2021)
n investigation on physicochemical characteristics of Bt (Seeni-1) vs local Hamid cultivar (cv) cottonseed oils (CSO) was conducted. Protein in Seeni-1 seed was relatively higher than Hamid cv seed. Oil content, ash and fibre of Hamid cv were relatively higher. Ash and oil content in black (chemical delinting) and white (mechanical delinting) seed were relatively higher in Hamid cv. There were no differences between the specific gravity (sp.gr.), refractive index (R.I.) and moisture content of both oils. Free fatty acids (FFA) and iodine value (IV) in Seeni-1 were relatively higher. Saturated fatty acids (SFAs) in Hamid cv oil proved to be more than Seeni-1 oil [automatically the USFA should be higher in Seeni-1]. Phosphorus content in Seeni-1 oil was lower than that of Hamid cv, whereas there was no significant difference in the peroxide value (PV).